2014
DOI: 10.1016/j.ahj.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pediatric cardiovascular clinical trials registered on ClinicalTrials.gov

Abstract: Background ClinicalTrials.gov is an NIH-sponsored registry of federally and privately funded trials. We sought to determine fundamental characteristics of registered pediatric cardiovascular trials (PCVTs). Methods A data set including 68134 interventional clinical trials was downloaded from ClinicalTrials.gov and entered into a relational database. Aggregate data from PCVTs were compared with other trial specialties. Multivariable logistic regression was used to evaluate factors associated with improved tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…The methods of defining derived variables have been described previously15 18 and are briefly summarised below. All trials were divided into six different groups by the funding sources according to the information in the ‘Sponsor_Collaborators’ and ‘Funded_By’ sections: NIH, industry, other, US federal (excluding NIH), university/college, hospital and other sources.…”
Section: Methodsmentioning
confidence: 99%
“…The methods of defining derived variables have been described previously15 18 and are briefly summarised below. All trials were divided into six different groups by the funding sources according to the information in the ‘Sponsor_Collaborators’ and ‘Funded_By’ sections: NIH, industry, other, US federal (excluding NIH), university/college, hospital and other sources.…”
Section: Methodsmentioning
confidence: 99%
“…Bourgeois examined several high disease burden conditions among children in high-, middle-, and low-income countries and found that 60% of disease burden was attributable to children, but only 12% of studies in ClinicalTrials.gov were pediatric trials [19]. Hill’s analysis of the portfolio on ClinicalTrials.gov [20] revealed a low number (116) of pediatric cardiovascular clinical trials relative to 2561 adult cardiovascular trials. Of the pediatric cardiovascular trials identified, approximately one-third were focused on diseases that may be amenable to testing a new drug, such as hypertension and dyslipidemia, rather than CHD.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer pediatric cardiovascular trials than in other pediatric specialties, and many important diseases remain understudied 48. It is therefore important to both increase the number of trials and conduct them with efficiency and at a reasonable cost.…”
Section: Approaches To Improving Clinical Trials In Children With Carmentioning
confidence: 99%